Обнаружение нового для фауны СССР вида ракушковых рачков (Crustacea, Ostracoda) - Голубничая, Л.В. (Вестник зоологии, 1968)
Five specimens of Limnocythere psammophila Flössne r, 1965 were found for the first time in the Soviet Union in Cherkassy and Kiev regions. Previously this species was known only for the German Democratic Republic. The specimens from the USSR only slightly differ from those. primarely described.